Skyrme-Hartree-Fock on Deformed Nucleus for the Island of Inversion Case - rizal kurniadi (Indonesian Journal of Physics, 2022)
The Island of Inversion is a state where the energy levels are not in a standard order. As a result, it will affect the calculation of several other physical quantities. One of those affected is the calculation of the radius of the nuclear charge. For this reason, this paper will present the analysis of the radius of the nucleus charge using the Skrme Hartree Fock method on a deformed nucleus. Through deformation effects, especially the quadruple effect, it is expected that the radius of the nuclear charge will increase. In this paper, we will present the calculation of the nucleus radius using the SHF deformed nucleus method and compare it with the SHF for the ground state nucleus. The calculation results show that this method can adequately handle the island of the inversion effect.